Knee isokinetic strength benchmarks in athletes across sports categories and performance levels - Freire, Raul; Huff, Drake; Butterick, Brooke; Figueroa, Elias C.; Siegler, Jason C. (Biology of Sport, 2025)
This study aimed to compare the isokinetic strength metrics (relative peak torque, hamstring/ quadriceps (H/Q) ratio, and bilateral asymmetry) between male and female athletes and performance levels (National and International) across sports categories ( Endurance, Power, Skill, Combat , and Team ). Secondly, this study presents reference values for knee isokinetic strength assessments for athletes from different sports. This cross-sectional study evaluated the knee isokinetic peak torque (PT) at 60o ·s −1 in 355 athletes (182 women, age 24.2±6.6 years, 173 men, age 24.3±9.1 years) from 24 different Olympic sports. Two-way ANOVA and eta-square effect size were used to compare sex and performance levels across sports categories. Consistently higher mean PT values were observed for all isokinetic variables in males than in females (Extension: 15%, Flexion: 7%). Higher PT values were found among male and female athletes in Combat (Extension: 12%, Flexion: 18%, ( p < 0.05) and Power (Extension: 11%, Flexion: 7%) ( p < 0.05), respectively. No differences were found between performance levels for all isokinetic strength metrics ( p = 0.10 to 0.98). H/Q ratio and bilateral asymmetry were not meaningfully affected by either sex or performance levels. In conclusion, male athletes demonstrated higher PT values than females, regardless of sports categories, suggesting PT benchmarks should be used across sports categories but not performance levels for male and female athletes.